Price-Level Determinacy, Lower Bounds on the Nominal Interest Rate, and Liquidity Traps - Ragna Alstadheim; Dale Henderson (Norges Bank, 2006)
We consider standard monetary-policy rules with inflation-rate targets and interest-rate or money-growth instruments using a flexible-price, perfect foresight model. There is always a locally-unique target equilibrium. There are also below-target equilibria (BTE) with inflation always below target and constant or asymptotically approaching or eventually reaching a below-target value. Liquidity traps are neither necessary nor sufficient for BTE which can arise if monetary policy keeps the interest rate above a lower bound. We construct monetary-policy rules, that preclude BTE, some of which are monotonic in inflation but all of which are non-differentiable at a point. For standard monetary-policy rules there are plausible fiscal policies that insure uniqueness by precluding BTE; those policies exclude perpetual surpluses and, possibly, perpetual balanced budgets.
hdl:11250/2498373
Keywords: E31; E41; E52; E62; 330; zero bound; liquidity trap; inflation targeting; determinacy